Inclusion of bilberry pomace in rabbit diets: Effects on carcass characteristics and meat quality. (February 2017) - Dabbou, Sihem; Gai, Francesco; Renna, Manuela; Rotolo, Luca; Dabbou, Samia; Lussiana, Carola; Kovitvadhi, Attawit; Brugiapaglia, Alberto; De Marco, Michele; Helal, Ahmed Noureddine; Zoccarato, Ivo; Gasco, Laura
Abstract: A trial was performed to evaluate bilberry pomace (BP) as alternative source of nutrients for rabbits. One hundred and forty-four Grimaud weaned rabbits were divided into 4 groups of 36 animals each and fed ad libitum with a basal diet (BP0) tested against three assay diets developed by substituting 50, 100 and 150 g/kg of the BP0 diet with BP (BP5, BP10 and BP15 diets, respectively). Carcass characteristics of rabbits were not affected by treatment, with the exception of liver weight. Dietary inclusion of BP did not affect proximate composition and oxidative status of longissimus thoracis et lumborum muscle. Dietary BP significantly ameliorated, in the same muscle, the nutritional quality and health properties of fat. Consumer acceptance of cooked rabbit meat was not significantly affected by treatment. In conclusion, BP can be included in rabbit diets to improve the lipid composition of meat, without adverse effects on carcass characteristics, other physico-chemical properties, oxidative status and meat sensorial traits.